Race me in a lobster suit : absurd internet ads and the real conversations that followed - Mahon, Kelly (Quirk Books, 2019)
"The internet is fun again! 'Knit me into a cocoon.' 'Feed me a burrito.' 'Race me in a lobster suit.' When New York City copywriter Kelly Mahon started posting fake gig ads online as a creative outlet, she was surprised to find that there was someone interested in every bizarre job offer she dreamed up. Race Me In a Lobster Suit collects Mahon's funniest posts, along witht the improvised email exchanges with would-be cocoon kintters and lobster racers. Some correspondents became suspicious, while others seemed willing to play along. The result is good-natured comedy gold and a kind of collaborative entertainment that could only exist in the internet gig economy"--Page[4] of cover.